Hubungan Derajat Insomnia dan Kejadian Migrain pada Mahasiswa Tingkat 3 Fakultas Kedokteran Universitas Islam Bandung - Fadhlan Rovie Effendie; Widayanti; Tryando Bhatara (UNISBA Press, 2023)
Abstract. The prevalence of insomnia and migraines is known to be high among university students. However, research that focuses on the relationship between the degree of insomnia and the incidence of migraine in medical students is still limited. To answer this question, this study focuses on the relationship between the degree of insomnia and the incidence of migraine among medical students. This study aims to describe the degree of insomnia and the description of the incidence of migraine as well as the relationship between the two variables in grade 3 students at the Faculty of Medicine, Islamic University of Bandung in 2022. The method used in this study was cross-sectional which was conducted on 75 research subjects by filling out the Insomnia Severity Index questionnaire. (ISI) and the Migraine Screen Questionnaire (MS-Q). The sampling technique used purposive sampling and statistical analysis using the Chi Square test. The results showed that the majority of research subjects experienced insomnia and migraines. These results indicate that there is a relationship between the degree of insomnia and the incidence of migraine in the study subjects. Abstrak. Prevalensi insomnia dan migrain diketahui tinggi pada kalangan mahasiswa. Namun penelitian yang berfokus pada hubungan derajat insomnia dan kejadian migrain pada mahasiswa kedokteran masih terbatas. Untuk menjawab persoalan tersebut, penelitian ini berfokus pada kaitan antara derajat insomnia dan kejadian migrain di kalangan mahasiswa kedokteran. Penelitian ini bertujuan untuk mengetahui gambaran derajat insomnia dan gambaran kejadian migrain serta hubungan antara kedua variabel pada mahasiswa tingkat 3 Fakultas Kedokteran Universitas Islam Bandung tahun 2022. Metode yang digunakan pada penelitian ini adalah cross sectional yang dilakukan pada 75 subjek penelitian melalui pengisian kuesioner Insomnia Severity Index (ISI) dan kuesioner Migraine Screen Questionnaire (MS-Q). Teknik pengambilan sampel menggunakan purposive sampling dan analisis statistik menggunakan uji Chi Square. Hasil penelitian menunjukkan mayoritas subjek penelitian mengalami insomnia dan migrain. Hasil tersebut menunjukkan terdapatnya hubungan antara derajat insomnia dan kejadian migrain pada subjek penelitian.